2018
DOI: 10.1186/s12978-018-0553-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to institutional delivery in rural areas of Chitwan district, Nepal: a qualitative study

Abstract: BackgroundGiving birth assisted by skilled care in a health facility plays a vital role in preventing maternal deaths. In Nepal, delivery services are free and a cash incentive is provided to women giving birth at a health facility. Nevertheless, about half of women still deliver at home. This study explores socio-cultural and health service-related barriers to and facilitators of institutional delivery.MethodsSix village development committees in hill and plain areas were selected in Chitwan district. We cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 39 publications
6
58
3
Order By: Relevance
“…This study found that mothers-in-law often close off this gap by providing psychosocial support by escorting the mothers to the health facility. Studies have shown the importance of psychosocial support to pregnant women in averting maternal and child health negative outcomes [24,25]. Our study also found that community members such as neighbours, local council village leaders and village extension health workers are instrumental in averting structural barriers to access to a health facility by sending for a boda-boda (motor cycle rider) in real time or other transport means to get the labouring mother to a health facility.…”
Section: Perceived Barriers To Uptake Of Health Facility Deliverymentioning
confidence: 54%
“…This study found that mothers-in-law often close off this gap by providing psychosocial support by escorting the mothers to the health facility. Studies have shown the importance of psychosocial support to pregnant women in averting maternal and child health negative outcomes [24,25]. Our study also found that community members such as neighbours, local council village leaders and village extension health workers are instrumental in averting structural barriers to access to a health facility by sending for a boda-boda (motor cycle rider) in real time or other transport means to get the labouring mother to a health facility.…”
Section: Perceived Barriers To Uptake Of Health Facility Deliverymentioning
confidence: 54%
“…Among studies included in the review, a majority was from India (n=30, 48 %) . There were 11 studies from Nepal (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) , 10 from Bangladesh (53)(54)(55)(56)(57)(58)(59)(60)(61)(62) , six from Indonesia (63)(64)(65)(66)(67)(68) and two from Timor-Leste 69,70 . From Bhutan 71 , Thailand 72 , and Myanmar 73 one from each was identi ed.…”
Section: Resultsmentioning
confidence: 99%
“…Involving FCHVs in these wide ranges of interventions would aid in the integration of maternal, child and newborn services thus leading better outcomes in human capital and development. It is however equally important to consider the work burden of FCHVs while task shifting and also capacitate FCHVs to deal with cultural and religious issues that surround during pregnancy and childbirth in Nepal [25,26].…”
Section: Discussionmentioning
confidence: 99%